Setting the Stage: A Critical Analysis of Performance-Based Approaches to Library Instruction - Hector, Emily (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2023)
Within scholarly and professional LIS literature, researchers and practitioners have applied the language, theory, and practices of stage performance to the context of academic library instruction. Recognizing the power of discourse in shaping professional norms and values, I wonder: How might the widespread presence of performance-based approaches to library instruction impact assumptions and expectations of those librarians who provide it? To better identify, interrogate, and imagine the implications of this discourse, this article first provides a review of the scholarship that has contributed to and resisted the phenomenon of library-instruction-as-performance, drawing upon the work of researchers who have engaged with theatrical, dramatic, or comedic approaches to library instruction. Using content analysis and close reading, I then analyze recent academic library conference programs to further understand how this thinking has been brought to life through professional development opportunities. Upon discovering a cluster of emotional themes within these texts, I follow how the discourse of performance in library instruction intersects with the concept of emotional labour in libraries, exploring how performance-based approaches can both demand emotional labour from and provide emotional reprieve to instruction librarians. In doing so, I focus on the interplay of professional discourse in library instruction and behavioural expectations of librarians—including their emotional expressions—to better understand how these phenomena co-exist and reinforce one another.